In vivo study of the effects of a portable cold plasma device and vitamin C for skin rejuvenation - Reza Shakouri (Nature Portfolio, 2021)
Abstract Nowadays, cold atmospheric plasma shows interesting results in dermatology. In the present study, a new portable cold plasma was designed for plasma skin rejuvenation (PSR) purposes. This device is safe and easy to use at beauty salons and homes. The effects of this device were investigated on the rat skins. Also, as a new method to improve PSR results, vitamin C ointment was combined with plasma. In this study, there were four groups of 5 Wistar rats. The first group received vitamin C ointment, the second received 5 min of high-voltage plasma, and the third and the fourth groups received 5 min of high- and low-voltage plasma and vitamin C ointment. This process was done every other day (3 sessions per week) for 6 weeks. To evaluate the thermal effect of plasma, the skin temperature was monitored. Also, the presence of reactive species was demonstrated by the use of optical spectroscopy. In addition, mechanical assays were performed to assess the effect of plasma and vitamin C on the tissue’s mechanical strength. The mechanical assays showed a positive impact of plasma on the treated tissue compared to the control group. Also, changes in the collagen level and thickness of the epidermal layer were examined in histological studies. The results indicated an increase in collagen levels after using plasma alone and an accelerated skin reaction after using vitamin C combined with plasma therapy. The epidermal layer’s thickness increased after applying high-voltage plasma, which indicates an increase in skin elasticity. This study demonstrates the positive effect of using the portable plasma device with vitamin C ointment on effective parameters in skin rejuvenation.